Economic crisis and Covid-19: Potential Effects on Criminality, Poverty and Mortality rates in Brazilian Municipalities - Raiher, Augusta Pelinski (Economía Sociedad y Territorio, 2021)
This paper aimed to analyze possible effects of the economic crisis caused by Covid-19 on criminality, poverty and mortality rates in Brazilian municipalities. With this purpose, the year 2015 was analyzed for being the period when the country went through the greatest recession in the recent years. The Propensity Score Matching Method was used to evaluate the impact of a sharp decrease in the GDP (Gross Domestic Product). The data surveyed showed that the recession did not occur in the same way in all municipalities, so that many of them were not affected by economic decline. In addition, two social aspects (mortality and poverty) did not present correlation with the GDP fall. Also, no difference of effect was observed in the variation of these variables between the municipalities that experienced the recession and those where there was economic growth. Therefore, if a sharp decrease in the GDP of some municipalities occurs, they will not necessarily have worse social aspect results than other Brazilian spaces.